Utilization of α-Keratin of Chicken Feathers as Adsorben of Lead Ion - Rais Nur Latifah; Roro Ernia; Edi Pramono (ALCHEMY Jurnal Penelitian Kimia, 2014)
Research of Pb ions adsorption with chicken feathers adsorbent has been conducted. This research aims to determine adsorption properties of activated chicken feathers and the chicken feathers that were not activatedby Na2S for Pb ions. The adsorption process was conducted by batch method with variation of the concentration, pH, and contact time. Pb content in solution is characterized by AAS spectroscopy (Atomic Absorption Spectroscopy). The results show that the contact time and pH condition for adsorption equilibrium are 60 min for activated chicken feathers and 90 min for chicken feathers which were not activated by Na2S at pH 8. Pb absorption by chicken feathers follows Freundlich isotherm and the reaction kinetics follow the Ho equation.